If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 1 = 5.2 Reorder the terms: 1 + 3y = 5.2 Solving 1 + 3y = 5.2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 3y = 5.2 + -1 Combine like terms: 1 + -1 = 0 0 + 3y = 5.2 + -1 3y = 5.2 + -1 Combine like terms: 5.2 + -1 = 4.2 3y = 4.2 Divide each side by '3'. y = 1.4 Simplifying y = 1.4
| -70+7=63 | | 4[d+f]= | | 0.625x-2=-12 | | 4/3(x-3)=8 | | 5x+7x-34=85-5x | | 8x+7=-3x-1 | | 2sin^2x-sinx+1=0 | | 9(z-913)=315 | | 21-5h=h+6 | | 13(-6x)+15=375 | | 14(t-910)=476 | | -5p+3=43 | | .80x+.20(70)=.70(70+x) | | .80x+.25(70)=.70(70+x) | | 4(s-859)=344 | | (x-2)=12(y-3) | | 2x+76=170 | | X+2y-7=6 | | (R/3)-4=11 | | x+2+x+4+x=180 | | 5x/3-2=13 | | 4(2-3b)=6b-4(b+5) | | 4(3x-2)-3=4(x-3)+33 | | 8m+20=2m | | 8(z-927)=256 | | 24a=6a*4 | | 300=x+75 | | 2y-7/y | | Y-7=14.1 | | 240=x-60 | | 25-6[(2-7)-(-5-7)]= | | 6(2x-5)=5(3x+7) |